2008
DOI: 10.1177/112972980800900105
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hemodynamic and Anatomic Parameters in a Swine Arteriovenous Fistula Model

Abstract: The described methodologies will allow the calculation and optimization of WSS profiles in animal models. This information could then be translated to the clinical setting where it would have a positive impact on improving the early maturation rates of AVFs as well as reducing the late venous stenoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Based on their patency, autogenous end-to-side and side-to-side fistuals are the favored types of a-v fistulas, providing optimal vascular access (Krishnamoorthy et al, 2008;Besarab et al, 2007). Complications in the fistula and the adjoining vessels can cause loss of access patency, burdening the patients with the need for re-operative treatment conferring additional costs to the health sector (Besarab et al, 2007;Saran et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Based on their patency, autogenous end-to-side and side-to-side fistuals are the favored types of a-v fistulas, providing optimal vascular access (Krishnamoorthy et al, 2008;Besarab et al, 2007). Complications in the fistula and the adjoining vessels can cause loss of access patency, burdening the patients with the need for re-operative treatment conferring additional costs to the health sector (Besarab et al, 2007;Saran et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…That low WSS is the major determinant of intimal thickness was demonstrated in vivo in dogs by Morinaga and colleagues in 1985 (34), who clearly showed that the change in WSS, but not the rate of blood flow, is the essential hemodynamic factor related to neointimal hyperplasia in autogenous vein grafts. Recently, a direct relation between low WSS profiles and patterns of neointimal hyperplasia was demonstrated in vivo in a pig model of AVF (35).…”
Section: Disturbed Flow As An Upstream Event In Neointimal Hyperplasiamentioning
confidence: 99%
“…MATERIALS AND METHODS AV fistula creation AV fistulae were created in two different configurations, namely, curved and straight, between the femoral artery and femoral vein in eight pigs, each weighing about 50 kg. 10 As surgical skills have been shown to be a determinant of AV fistula success or failure in the human setting, all the surgeries were performed by a single surgeon (YW).…”
Section: Discussionmentioning
confidence: 99%
“…7 At a radiological level, AV fistula non-maturation is characterized by a peri-anastomotic venous segment stenosis. 8 At a mechanistic level, the exact reasons for either AV fistula success (maturation) or failure (non-maturation) are unclear, but it is likely that the magnitude of stenosis is influenced, both by the amount of neointimal hyperplasia 9,10 and also by the ability or inability of the venous segment to dilate following creation of the AV anastomosis.…”
mentioning
confidence: 99%